Age-Related Serum Thyroid-Stimulating Hormone Reference Range in Older Patients Treated with Levothyroxine: A Randomized Controlled Feasibility Trial (SORTED 1). Issue 1 (21st January 2020) - Razvi, Salman; Ryan, Vicky; Ingoe, Lorna; Pearce, Simon H.; Wilkes, Scott
Abstract : Introduction: Serum thyroid-stimulating hormone (TSH) increases with age but target TSH is similar in younger and older hypothyroid patients on treatment. It is unknown if quality of life (QoL), hypothyroid symptoms and cardiovascular risk factors change in older hypothyroid patients treated to an age-appropriate reference range. Objective: To assess if a higher target serum TSH of 4.01–8.0 mU/L is feasible in, and acceptable to, older treated hypothyroid patients. Methods: A single-blind (participant) randomised controlled feasibility trial involving 48 hypothyroid patients aged ≥80 years on established and stable levothyroxine (LT4) therapy with serum TSH levels within the standard reference range (0.4–4.0 mU/L) was conducted. Standard (0.4–4.0 mU/L) or higher (4.1–8.0 mU/L) TSH target (standard TSH [ST] or higher TSH [HT] groups) LT4 for 24 weeks was administered. The outcome measures evaluated were thyroid function tests, QoL, hypothyroid symptoms, cardiovascular risk factors and serum marker of bone resorption in participants that completed the trial ( n = 21/24 ST group, n = 19/24 HT group). Results: At 24 weeks, in the ST and HT groups, respectively, median (interquartile range) serum TSH was 1.25 (0.76–1.72) and 5.50 (4.05–9.12) mU/L, mean (± SD) free thyroxine (FT4) was 19.4 ± 3.5 and 15.9 ± 2.4 pmol/L, and daily LT4 dose was 82.1 ± 26.4 and 59.2 ± 23.9 µg. There was no suggestion of adverse impact of a higher serum TSH in the HT group with regard to any of the outcomes assessed. Conclusions: In hypothyroid patients aged ≥80 years on LT4 therapy for 24 weeks, there was no evidence that a higher target serum TSH was associated with an adverse impact on patient reported outcomes, cardiovascular risk factors or bone resorption marker over 24 weeks. Longer-term trials assessing morbidity and mortality outcomes and health-utility in this age group are feasible and should be performed.